Revolution 4.0, Skills, Education and Guidance - Echeverría Samanes, Benito (2018)
We are witnessing the birth of the fourth industrial revolution, which is blurring the boundaries between the physical, digital, and biological spheres. It is transforming productive, economic, and commercial relations, to the point of radically changing the way we live, work, and relate to each other. It is not only changing what and how we do things, but also who we are. Numerous studies agree that the new scenario will require new competences not only of a technical and methodological nature but also and above all of a participatory and personal nature. Those “cross-sectional competences,” widely generalizable and transferable, required in different contexts and different activities, and which are apprehended through different experiences. Education is the most powerful tool that can be used to respond to the unavoidable need to update and improve the competences of an ever‑growing number of people and, additionally, all throughout their lives. An education that fosters learning or unlearning in order to relearn in the VUCA world. In this world, the guiding intervention that favors the clarification of personal possibilities with meaning is essential, so that every human being can become who they are, without being trapped in cognitive, procedural, and attitudinal patterns of the past.